Antioxidant activities and anticancer screening of ethanolic extracts from Baccaurea macrophylla Muell and Elateriospermum tapos Blume - Tisadondilok, Sita; Senawong, Thanaset (Interdisciplinary Research Review, 2018)
Two local plants in Euphorbiaceae family, Baccaurea macrophylla Muell.(Langkha) and Elateriospermum tapos Blume. (Pra), are traditionally used in local cuisine and herbal medicines in Thailand.In this study, ethanolic extracts prepared from fruits, leaves, seeds and stem barks of these plants were tested for antioxidant properties using DPPH assay and also screened for anticancer activity using MTT assay against four human cancer cell lines: breast (MCF-7), colon (HT29, HCT116) and cervical (HeLa). The ethanolic crude extracts from the leaves of Pra and Langkha showed the highest total phenolic contents (TPC) (198.77±6.26 and 161.17± 0.32 mg gallic acid equivalent (GAE)/1 g of sample, respectively) compared to the other parts of the plants. Whereas, the ethanolic extracts of Pra’s seed and Langkha’s dried pulp had the lowest amounts of TPC (0.76± 0.42 and 1.06± 0.12 mg GAE/1 g of sample, respectively). In addition, E. tapos fresh leaf and B. macrophylla dried leaf ethanolic extracts exhibited the highest antioxidant activities with IC50 values of 0.10 and 1.70 μg/mL, respectively. The dried leaf ethanolic extract of E. tapos had the highest cytotoxicity against HeLa, HCT116, and MCF-7 cells (97.44, 98.58, 98.57% inhibition, respectively, at 100 μg/mL), whereas its seed skin ethanolic extract had the highest cytotoxic activity against HT29 cells (98.76% inhibition at 100 μg/mL) for 72 h-exposure. Among all ethanolic extractsof B. macrophylla, its dried leaf ethanolic extract had the highest cytotoxicity against all cancer cell lines tested. The leaf ethanolic extracts of E. tapos had greater anticancer activity than those of B. macrophylla.